2008
DOI: 10.1111/j.1460-9568.2008.06381.x
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory of the recent past following frontal cortex or temporal lobe excisions

Abstract: Previous research has raised questions regarding the necessity of the frontal cortex in autobiographical memory and the role that it plays in actively retrieving contextual information associated with personally relevant events. Autobiographical memory was studied in patients with unilateral excisions restricted to the frontal cortex or temporal lobe involving the amygdalo-hippocampal region and in normal controls using an event-sampling method. We examined accuracy of free recall, use of strategies during ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
1
17
3
Order By: Relevance
“…Crucially, our results are at odds with a similar study showing a disruption in the temporal ordering of AM details during free recall in patients with unilateral medial temporal lobe excision (Thaiss and Petrides, 2008). In that study, fewer TLE patients than healthy controls adopted temporal ordering strategies spontaneously when listing activities they performed over a 2-day period, as determined by a blind external rater.…”
Section: The Mtl and Temporal Ordercontrasting
confidence: 77%
See 2 more Smart Citations
“…Crucially, our results are at odds with a similar study showing a disruption in the temporal ordering of AM details during free recall in patients with unilateral medial temporal lobe excision (Thaiss and Petrides, 2008). In that study, fewer TLE patients than healthy controls adopted temporal ordering strategies spontaneously when listing activities they performed over a 2-day period, as determined by a blind external rater.…”
Section: The Mtl and Temporal Ordercontrasting
confidence: 77%
“…A recent study by Thaiss and Petrides (2008) has also demonstrated that, in comparison to healthy controls, unilateral TLE patients are impaired at ordering events in time during the free recall of week-old AMs; patients also used temporal organization strategies less spontaneously than healthy controls. Taken together, evidence suggests that information about the temporal structure of AM is supported by the medial temporal lobe, especially the hippocampus.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…1). Recall of episodes from the recent past was impaired (see also Thaiss and Petrides 2008). Yet, other patients produced fewer details about past events, even events from early life (Rosenbaum et al 2005;Steinvorth et al 2005;Race et al 2011).…”
Section: Studies Of Retrograde Amnesia In Memory-impaired Patientsmentioning
confidence: 98%
“…context) but not for item has been reported following large frontal lesions [9][10][11][12], suggesting a critical role of the prefrontal cortex in context retrieval. However, source memory impairments have not always been reported in patients with lesions clearly restricted to the prefrontal cortex [13,14], raising the question of the precise conditions under which context retrieval depends on different parts of the large and anatomically heterogeneous prefrontal cortex.…”
Section: Introductionmentioning
confidence: 99%